2015
DOI: 10.3171/2014.11.spine14181
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous “K-wireless” pedicle screw fixation technique: an evaluation of the initial experience of 100 screws with assessment of accuracy, radiation exposure, and procedure time

Abstract: OBJECT Percutaneous pedicle screws are used to provide rigid internal fixation in minimally invasive spinal procedures and generally require the use of Kirchner wires (or K-wires) as a guide for screw insertion. K-wires can bend, break, advance, or pull out during the steps of pedicle preparation and screw insertion. This can lead to increased fluoroscopic and surgical times and potentially cause neurological, vascular, or visceral injury. The authors present their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 51 publications
3
36
1
1
Order By: Relevance
“…However, K-wires are associated with the added morbidity of potential violation of the retroperitoneum and malfunctions such as bending, breaking, and decannulating. 19,20 Recently, a ''K-wireless'' percutaneous pedicle screw placement technique was published by Spitz et al 21 that uses intraoperative fluoroscopy for localization. This method is technically feasible and provides a safe alternative to the use of K-wires.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, K-wires are associated with the added morbidity of potential violation of the retroperitoneum and malfunctions such as bending, breaking, and decannulating. 19,20 Recently, a ''K-wireless'' percutaneous pedicle screw placement technique was published by Spitz et al 21 that uses intraoperative fluoroscopy for localization. This method is technically feasible and provides a safe alternative to the use of K-wires.…”
Section: Introductionmentioning
confidence: 99%
“…This method is technically feasible and provides a safe alternative to the use of K-wires. 21 At our institution, we have modified the Spitz technique by using intraoperative image-guided stereotactic navigation rather than fluoroscopy for pedicle screw placement to provide increased speed and precision, all while reducing the radiation exposure of operating personnel. Information on the K-wireless technique is limited, and, to our knowledge, using intraoperative image-guided stereotactic navigation has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports in patients with spinal trauma, however, have supported the use of minimally invasive techniques in the trauma population 12 13. Furthermore, when compared to open surgery, percutaneous pedicle screw fixation has been associated with significantly reduced intraoperative blood loss, decreased days on a ventilator, decreased ICU length of stay and shorter length of overall hospital stay 9 14…”
Section: Discussionmentioning
confidence: 99%
“…The concept of pars defect reconstruction involves the consolidation of the isthmus by different osteosynthesis techniques and became an alternative to in situ segmental spinal fusion. 3,24,27 On the other hand, Westacott et al 26 revealed little clinical difference between pars repair and fusion techniques. The advantage of this procedure is preservation of motion over the spondylolytic level in young patients taking into consideration the disc status in Magnetic Resonance Imaging (MRI) finding.…”
Section: Introductionmentioning
confidence: 99%